Structure, photoluminescence, and photocatalytic activity of TiO2@Au/Sm3+ nanocomposites for dyes remediation - O. M. Lavrynenko; M. M. Zahornyi; E. Paineau (Хімія, фізика та технологія поверхні)
The textile industries produce a lot of toxic dyes and pigments that can absorb and reflect sunlight in the water. The application of heterogeneous photocatalysis for the removal of these pollutants is effective using metal-oxide-based nanocomposites with noble and rare earth metals under different light irradiation. The effect of dopant concentration on the structural, optical, and electronic properties of TiO2 nanomaterials is also important for their photocatalytic performance. The synthesis of TiO2&Au/Sm particles with a gold content of 2 and 4 wt. % and samarium 0.2 wt. % was carried out by the chemical precipitation of a TTIP (titanium tetraisopropoxide) solution in the presence of Sm3+ and Au3+ cations. The primary particle size CSR (coherent scattering region) of nanopowders was 18–20 nm. It has been shown that gold is included in the composite structure, with an increase in the parameters of the anatase crystal lattice. The presence of samarium in the composite structure was confirmed by EDS and PL methods. The obtained structures have shown high sorption activity to cationic dyes (Methylene Blue and Rhodamine B), lower – to anionic ones, in particular, Orange G. It is shown that under the influence of UV irradiation, the solutions undergo decolorization, which is accompanied by the destruction of dye molecules, which is confirmed by the hypsochromic shift of the characteristic maximum in the UV-VL spectra. The series OG (46.7 %) < MO (89.2 %) < MB (96.0 %) < RhB (98.5 %) for TiO2&Au/Sm particles ([Au] = 2 wt. %, [Sm] = 0.2 wt. %) and MO (22.6 %) < RhB (24.1 %) < OG (41.5 %) < MB (98.6 %) for TiO2&Au/Sm ([Au] = 4 wt. %, [Sm] = 0.2 wt. %) particles were found according to the intensity of decolorization of the dye solutions. The difference in the course of the photocatalytic process can be related to the PZC (point of zero charge) of the composite particles, which is 7.01 ([Au] = 2 wt. %) and 9.25 ([Au] = 4 wt. %).